1998
DOI: 10.1016/s0954-6111(98)90315-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of malignant pleural effusion: pleurodesis using a small percutaneous catheter. A prospective randomized study

Abstract: The aim of this prospective, randomized study was to investigate the possibility of performing pleurodesis using a small percutaneous catheter (Cystofix catheter, CH10, 65 cm) inserted at bedside in patients with recurrent malignant pleural effusion and to compare this catheter with a conventional large bore chest tube (CH24) placed in connection with diagnostic thoracoscopy. After drainage pleurodesis was performed with tetracycline as sclerosing agent. Of 18 evaluable consecutive patients (mean age 67.8 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(91 citation statements)
references
References 8 publications
2
85
0
4
Order By: Relevance
“…The pain brought by chest tube drainage was reckoned the biggest weakness and most of the patients experienced short-lasting but intense pain when the chest tube drainage was removed (60). Some trials found small-bore chest tube drainages had the similar success rate to larger drainage but being less painful (61). To manage the inevitable pain, one of the most common complications of chest tube drainage insertion, we needed more details to notice and perform.…”
Section: Discussionmentioning
confidence: 99%
“…The pain brought by chest tube drainage was reckoned the biggest weakness and most of the patients experienced short-lasting but intense pain when the chest tube drainage was removed (60). Some trials found small-bore chest tube drainages had the similar success rate to larger drainage but being less painful (61). To manage the inevitable pain, one of the most common complications of chest tube drainage insertion, we needed more details to notice and perform.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several recent studies support the concept that LBCTs are directly associated with higher thoracic pain (14)(15)(16)(17). Moreover, the risk of infection appears to be higher when a large-bore drain is used, especially for prolonged placements (18).…”
Section: Large-bore Drainsmentioning
confidence: 95%
“…They found that these small-caliber catheters had a performance similar to large-caliber tubes, but with substantially reduced pain levels. The advantages of small-caliber catheters have subsequently been confirmed in numerous studies (Grodzin and Balk, 1997;Clementsen et al, 1998;Putnam et al, 2000;Parulekar et al, 2001) and the British Thoracic Society (BTS) guidelines for the management of malignant pleural effusions (Antunes et al, 2003) recommend the use of small-caliber catheters in lieu of larger-caliber chest tubes.…”
Section: Introductionmentioning
confidence: 95%